Essential role of PET-CT in the management of patients with severe infectious complication CIEDS: multicentre study. (25th November 2020) - Taborsky, M; Latal, J; Fedorco, M; Skala, T; Novak, M; Kozak, M; Krivan, L; Gloger, V; Schee, A
Abstract: Background: With the increasing number of implanted cardiac pacemakers, ICDs and CRTs, the number of serious infectious complications of these procedures increases significantly, especially in the longer term from the primary implantation. The systematic solution is in most cases endovasal extraction of these systems. Methods: In a multicenter, prospective, randomized, controlled trial evaluating the benefit of CIEDS infection management in 277 patients, a conventional approach using blood cultures, microbiological examinations and TEE versus innovative management of these patients using PET-CT was compared. PET-CT examination is able to differentiate very well the infection of the implant pocket (Figure A) against bacterial endocarditis (Figure B). Thanks to this, it is possible to individualize the management of the patient and to shorten the dates of hospitalization, resp. time to re-implantation of the new system in patients without the presence of bacterial endocarditis. Results: The results of the multicentre study are summarized in Table 1. Conclusions: A comprehensive examination of patients with CDRIE using PET-CT significantly shortens hospital stay, time of antibiotic therapy and, as a consequence, leads to a lower incidence of serious complications of extraction procedures. Funding Acknowledgement: Type of funding source: None